Randomized clinical effectiveness trial of nurse-administered small-group cognitive behavior therapy for persistent insomnia in general practice. - Espie, C; MacMahon, K; Kelly, H; Broomfield, N; Douglas, N; Engleman, H; McKinstry, B; Morin, C; Walker, A; Wilson, P (2007)
STUDY OBJECTIVES: Persistent insomnia, although very common in general practice, often proves problematic to manage. This study investigates the clinical effectiveness and the feasibility of applying cognitive behavior therapy (CBT) methods for insomnia in primary care. DESIGN: Pragmatic randomized controlled trial of CBT versus treatment as usual. SETTING: General medical practice. PARTICIPANTS: Two hundred one adults (mean age, 54 years) randomly assigned to receive CBT (n = 107; 72 women) or treatment as usual (n = 94; 65 women). INTERVENTION: CBT comprised 5 sessions delivered in small groups by primary care nurses. Treatment as usual comprised usual care from general practitioners. MEASUREMENTS AND RESULTS: Assessments were completed at baseline, after treatment, and at 6-month follow-up visits. Sleep outcomes were appraised by sleep diary, actigraphy, and clinical endpoint. CBT was associated with improvements in self-reported sleep latency, wakefulness after sleep onset, and sleep efficiency. Improvements were partly sustained at follow-up. Effect sizes were moderate for the index variable of sleep efficiency. Participants receiving treatment as usual did not improve. Actigraphically estimated sleep improved modestly after CBT, relative to no change in treatment as usual. CBT was also associated with significant positive changes in mental health and energy/vitality. Comorbid physical and mental health difficulties did not impair sleep improvement following CBT. CONCLUSION: This study suggests that trained and supervised nurses can effectively deliver CBT for insomnia in routine general medical practice. Treatment response to small-group service delivery was encouraging, although effect sizes were smaller than those obtained in efficacy studies. Further research is required to consider the possibility that CBT could become the treatment of first choice for persistent insomnia in primary healthcare.